Water governance, policy and knowledge transfer : international studies in contextual water management - Boer, Cheryl de (Earthscan studies in water resource management., 2013)
In an increasingly global community of researchers and practitioners, new technologies and communication means have made the transfer of policies from one country or region to another progressively more prevalent. There has been a lot of attention in the field of public administration paid to policy transfer and institutional transplantation. This book aims to create a better understanding of such transfers in the water management sector. These include the adoption of modern water management concepts, such as integrated water resources management and forms of water governance, which are str.